The influence of the Buddhist way of life led to the emergence of Thai dancing arts and culture: The influence of the Buddhist way of life led to the emergence of Thai dancing arts and culture - Sripen, Sarunyaput (RATANABUTH JOURNAL, 2023)
Buddhism is considered a religion that has been important to the lives of Thai people in all regions for many centuries, affecting the lives of Thai people since the past. Living in modern times focuses on the pursuit of happiness in life. Whether it’s physical happiness and mental happiness. However, the way of living according to Buddhist principles has affected the birth of Thai dancing arts that focus on physical and mental happiness in various ways. Depending on the context, different areas of the region of Thailand lead to the emergence of artistic and dramatic arts that the author will present, consisting of the northern region, which is a candle dance to offer to the Lord Buddha according to the views of the Lanna Thai people, etc. The eastern region north It is a Mor Lam Klon performance. In that verse, you will find the verse that says the worship of superhuman beings in the form of praying for blessings from the sacred things that belong to Buddhism, such as the Buddha, the Noble Sangha in Buddhism. traditional performing arts Concealed the essence of religious teachings and the southern region as a manorah, which is both expressed as a story and based on beliefs that are rituals. In a case study of the Sunday Buddhist Study Center led by Phrakhru Adulvirakhom, the abbot of Chonlatharawat Temple, Tanyongmat Subdistrict, Rangae District, Narathiwat Province, etc.